Waves of attention: patterns and themes of international antimicrobial resistance reports, 1945–2020. Issue 11 (5th November 2021) - Overton, Kristen; Fortané, Nicolas; Broom, Alex; Raymond, Stephanie; Gradmann, Christoph; Orubu, Ebiowei Samuel F; Podolsky, Scott H; Rogers Van Katwyk, Susan; Zaman, Muhammad H; Kirchhelle, Claas
Abstract : This article uses quantitative and qualitative approaches to review 75 years of international policy reports on antimicrobial resistance (AMR). Our review of 248 policy reports and expert consultation revealed waves of political attention and repeated reframings of AMR as a policy object. AMR emerged as an object of international policy-making during the 1990s. Until then, AMR was primarily defined as a challenge of human and agricultural domains within the Global North that could be overcome via 'rational' drug use and selective restrictions. While a growing number of reports jointly addressed human and agricultural AMR selection, international organisations (IOs) initially focused on whistleblowing and reviewing data. Since 2000, there has been a marked shift in the ecological and geographic focus of AMR risk scenarios. The Global South and One Health (OH) emerged as foci of AMR reports. Using the deterritorialised language of OH to frame AMR as a Southern risk made global stewardship meaningful to donors and legitimised pressure on low-income and middle-income countries to adopt Northern stewardship and surveillance frameworks. It also enabled IOs to move from whistleblowing to managing governance frameworks for antibiotic stewardship. Although the environmental OH domain remains neglected, realisation of the complexity of necessary interventions has increased the range of topics targeted by international action plans. Investment nonetheless continues to focus on biomedical innovation and tends to leave aside broader socioeconomic issues. Better knowledge of how AMR framings have evolved is key to broadening participation in international stewardship going forward.